2013
DOI: 10.1530/eje-13-0488
|View full text |Cite
|
Sign up to set email alerts
|

Prostate volume and growth during testosterone replacement therapy is related to visceral obesity in Klinefelter syndrome

Abstract: Objective: Klinefelter syndrome (KS) is a chromosomal alteration characterized by increased risk of metabolic syndrome, mainly caused by visceral obesity. In the last years, obesity has been studied as a potential risk factor for prostate disease and recently a link has been demonstrated between visceral adiposity with prostate volume. The aim of this study was to analyze the relationship between obesity and prostate volume and growth during testosterone therapy in KS subjects. Design and methods: We evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
0
13
0
1
Order By: Relevance
“…A single study found triglycerides to decrease after testosterone treatment, but this might be caused by selection bias as the population as a whole at baseline had a mean triglycerides level at 117.6 ± 169.9 mg/dL, while the subset of patients followed before and after treatment at baseline had a mean triglyceride level of 311.5 ± 500.5. It is thus significantly higher than the population as a whole and the normal reference range <150 mg/dL provided by the authors (114).…”
Section: Lipidsmentioning
confidence: 57%
See 1 more Smart Citation
“…A single study found triglycerides to decrease after testosterone treatment, but this might be caused by selection bias as the population as a whole at baseline had a mean triglycerides level at 117.6 ± 169.9 mg/dL, while the subset of patients followed before and after treatment at baseline had a mean triglyceride level of 311.5 ± 500.5. It is thus significantly higher than the population as a whole and the normal reference range <150 mg/dL provided by the authors (114).…”
Section: Lipidsmentioning
confidence: 57%
“…In another study, both mean serum insulin and HOMA were numerically higher in treated versus untreated KS (no statistics applied) (98), and in yet another study, KS on testosterone treatment had lower HOMA-IR than the untreated group (87), indicating some effect of treatment. Similarly, HOMA-IR, but not serum insulin, was reduced in a group of 56 men with KS after 18 months of testosterone treatment (114). Thus, the data on the effect of testosterone treatment on features of carbohydrate metabolism in KS are somewhat conflicting.…”
Section: Glucose and Insulinmentioning
confidence: 99%
“…Furthermore, in men with Klinefelter's syndrome (primary hypogonadism) treated with testosterone to eugonadal levels, only men with a waist circumference > 94 cm had a significant increase in prostate size; 41 the implication being that visceral obesity (one of the most significant components of metabolic syndrome) is associated with prostate volume and influences prostate growth during TRT.…”
Section: Metabolic Syndrome Lower Urinary Tract Symptoms and Testostmentioning
confidence: 99%
“…[23,37] наблюдали лишь некоторое улучшение композиционного состава тела после гормональной терапии у пациентов с СК. Имеются сообщения и об отсутствии значительных изменений после терапии [40,41].…”
Section: ожирениеunclassified